THE METHODOLOGY OF IMPLEMENTATION OF CLUSTER APPROACH IN REGIONAL ECONOMY DEVELOPMENT - Vladimir Ryabov; Akop Abelian (Вестник Северо-Кавказского федерального университета, 2022)
The main approaches of clustering in the development of regional economy are revealed. The article investigates the main approaches to the formation of the regional economy based on the analysis of the interaction of enterprises considering their capabilities and the creation of competitive advantages in the process of creating clusters on innovative principles of functioning in the long term of its existence. A set of elements based on the choice of a cluster strategy is proposed. Developed a system of forming the combinations forming the new cluster system of the regional economy.